Aluminum metal matrix composites a review of reinforcement; mechanical and tribological behavior - Dev Srivyas, Pranav; S. Charoo, M (International Journal of Engineering and Technology, 2018)
This review aims to explore the fundamental mechanical and tribological behavior Aluminum matrix composites (AMCs) reinforced with different reinforcements. Aluminum matrix composites are considered to be the new emerging class of materials which are having the tailored properties for specific applications. AMCs are the advanced engineering materials having superior properties as comparison to other conventional aluminum alloys. AMCs exhibits attractive properties such as high hardness, better yield strength, strength to weight ratio, high thermal conductivity, low coefficient of thermal expansion, superior wear and corrosion resistance. In recent times, because of these properties they have repealed keen interest for various potential applications in aerospace, automotive and various other structural applications.. Extensive research and development has been made in the Al-based MMCs with every possible alloy and different reinforcements so as to get the material of desired properties. By suitable use of different reinforcements in the Al metal matrix a wide range of properties combination can be obtained. The fundamental mechanical and tribological behavior of different reinforcements under dry and wet lubricated sliding conditions is recently being studied. It is reported that various reinforcement were successfully employed to decrease friction and wear in various applications. A comprehensive review is provided with the aim to analyze such properties of different reinforcements.Â